The use of remote sensing of the Earth to assess the natural and anthropogenic transformations of lakes in the Polissya region - Martyniuk, Vitalii; Tomchenko, Olha (Scientific Centre for Aerospace Research of the Earth Institute of Geological Science National Academy of Sciences of Ukraine, Kyiv, Ukraine, 2021)
The problem of transformation of lakes of Polissya region under the influence of global climate changes, and also anthropogenic factors in basin systems (drainage reclamation, agrarian nature use and chemicalization of watershed soils, growth of residential lands, uncontrolled extraction of water from underground horizons, unauthorized extraction of amber, etc.), which lead to the reduction of water bodies, acceleration of sedimentation, eutrophication and, as a consequence, transformation into lake-swamp complexes are substantiated. The main stages of field researches, features of decryption of lakes by space images, the essence of the concept of «paleo-lake» and natural aquatic complex (NAC) have been revealed. An algorithm scheme of research of natural-anthropogenic transformations of the lake with the use of remote sensing and GIS technologies has been proposed. With the help of the Google Earth resource the estimation of changes of parameters of the areas of model lakes of Volyn Polissya is carried out, and on an example of Bilske lake the changes in the area of the reservoir from the «paleo-lake» to the modern boundaries of the shoreline and water area have been analyzed. The hydrological and limnological parameters of Bilske lake have been analyzed. Based on the analysis of high-resolution space images (Sentinel-1, Sentinel-2, Landsat) in different spectral channels, the ecological condition of the lake has been assessed by the vegetation index (NDVI), the dynamics of the thermal regime of the lake surface has been analyzed and the reservoir temperature changed during 2017-2021. A digital landscape map of Bilske lake, with the separation of aqua facies has been presented and landscape-assessment of NAC has been done. In the course of the research, the tendency to increase of temperatures of a reservoir has been established. The proposed approach using remote sensing tools to assess the ecological status of lakes is effective in methodological and practical terms. Along with instrumental and laboratory methods, it is expedient to use it for the creation of ecological passports of reservoirs, monitoring of lakes of reserved and recreational territories, long-term forecasting of development of aquatic complexes in the conditions of natural and anthropogenic transformations.